Efeito de herbicidas na dessecação e germinação de sementes remanescentes de Lolium multiflorum L. - de Campos, Caio Ferraz [UNESP]; Martins, Dagoberto [UNESP]; Peres Rodrigues da Costa, Andreia Cristina; Rocha Pereira, Maria Renata; Cardoso, Leonildo Alves; Martins, Cibele Chalita [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
A trial was carried out to evaluate efficacy of different herbicides and spray volumes when sprayed to ryegrass for chemical management and control of remaining seeds. The treatments were: three formulations of glyphosate at 1080 g ha(-1) (Original Round up, Round up Transorb, WG Round Up), paraquat + diuron at 300+500 and 150+250 g ha(-1) and glufosinate ammonium at 400 and 600 g ha(-1). All treatments were used in spray volumes of 200 and 400 l ha(-1). The effectiveness of the desiccation of ryegrass plants was assessed at 1, 3, 7, 14 and 21 days after application. At the last evaluation samples were collected for dry mass production analysis, and also panicles with seeds for germination test. Glyphosate in different formulations and volumes and glufosinate ammonium at 600 g ha(-1) when sprayed with into 400 l ha(-1) provided the best controls regarding ryegrass chemical management. Treatments with gliphosate (Roundup Original) and paraquat + diuron (300 +150 g ha(-1)) in volumes of 400 and 200 L ha(-1), respectively, were the ones that showed the lowest values of dry matter, differing from the control. All the ryegrass seeds were killed by treatments with herbicides (paraquat + diuron) at 500 + 250 g ha(-1) and glufosinate-ammonium at 600 g ha(-1) when used 200 l ha(-1).
Effect of herbicides on desiccation of Lolium multiflorum L. plants and seed germination
Keywords: Ryegrass; Control; Spraying technology; Herbicide